Impact of PM2.5 exposure on mortality and tumor recurrence in resectable non-small cell lung carcinoma - Bongkotmas Kosanpipat; Thanida Wongwut; Natthawat Norrasan; Parada Watthanawongsa; Phichayut Phinyo; Somcharoen Saeteng; Sophon Siwachat; Busyamas Chewaskulyong; Apichat Tantraworasin (Scientific Reports)
Abstract This study aimed to explore the impact of PM 2.5 exposure on survival, post-operative outcomes, and tumor recurrence in resectable non-small cell lung cancer (NSCLC) patients. The study cohort comprised 587 patients at Chiang Mai University Hospital between January 1, 2010, and December 31, 2017. Patients were categorized based on their residents’ average PM 2.5 concentration into two groups: exposed (PM 2.5 ≥ 25 µg/m3 annual mean) and unexposed (PM 2.5 < 25 µg/m3 annual mean). The exposed group had 278 patients, while the unexposed group had 309 patients. Baseline differences in gender and surgical approach were observed between the groups. Multivariable regression analysis revealed that patients in the exposed group had a higher risk of death (HR 1.44, 95% CI, 1.08–1.89, p = 0.012). However, no significant associations were found between PM 2.5 and post-operative pulmonary complications (RR 1.12, 95% CI, 0.60–2.11, p = 0.718), in-hospital mortality (RR 1.98, 95% CI, 0.40–9.77, p = 0.401), and tumor recurrence (HR 1.12, 95% CI, 0.82–1.51, p = 0.483). In conclusion, a PM 2.5 concentration ≥ 25 µg/m3 annual mean was associated with decreased overall survival and a potential increase in in-hospital mortality among resectable NSCLC patients. Larger studies with extended follow-up periods are required to validate these findings.